2019
DOI: 10.3389/fspas.2019.00044
|View full text |Cite
|
Sign up to set email alerts
|

How Many Twists Do Solar Coronal Jets Release?

Abstract: Highly twisted magnetic flux ropes, with finite length, are subject to kink instabilities, and could lead to a number of eruptive phenomena in the solar atmosphere, including flares, coronal mass ejections (CMEs) and coronal jets. The kink instability threshold, which is the maximum twist a kink-stable magnetic flux rope could contain, has been widely studied in analytical models and numerical simulations, but still needs to be examined by observations. In this article, we will study twists released by 30 off-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 54 publications
(68 reference statements)
1
13
0
Order By: Relevance
“…Specifically, the statistical studies carried out by Moore et al [64,186] found the existence of obvious axial rotation in both standard and blowout jets; their results showed that the number of turns of axial rotation ranged from 0.25 to 2.5. Other case studies showed that the number of turns of axial rotation ranged from about 0.34 to 4.7 [187190], and the periods were measured to be 1–20 min [174,191,192].…”
Section: Observational Featurementioning
confidence: 99%
“…Specifically, the statistical studies carried out by Moore et al [64,186] found the existence of obvious axial rotation in both standard and blowout jets; their results showed that the number of turns of axial rotation ranged from 0.25 to 2.5. Other case studies showed that the number of turns of axial rotation ranged from about 0.34 to 4.7 [187190], and the periods were measured to be 1–20 min [174,191,192].…”
Section: Observational Featurementioning
confidence: 99%
“…With respect to the kink instability, the widely adopted critical value was proposed by Hood & Priest (1981), where they considered a line-tying, force-free, uniform twisted flux rope and found that an MFR would become kink unstable when its twist exceeds 1.25 turns. However, both theories (Hood & Priest 1979, 1980Bennett et al 1999;Baty 2001;Török et al 2004;Török & Kliem 2005;Zaqarashvili et al 2010) and observations (Wang et al 2016;Liu et al 2019) and so on. Based on the previous works (Dungey & Loughhead 1954;Hood & Priest 1979;Bennett et al 1999;Baty 2001), the critical twist is proportional to the aspect ratio of an MFR, namely,…”
Section: Existence Of Highly Twisted Flux Ropes Before Eruptionmentioning
confidence: 99%
“…Specifically, the statistical studies made by Moore et al [64,186] found the existence of obvious axial rotation in both standard and blowout jets; their results showed that the number of turns of axial rotation ranges from 0.25 to 2.5. Other case studies showed that the number of turns of axial rotation ranges from about 0.34 to 4.7 [187][188][189][190], and the periods were measured to be 1-20 minutes [174,191,192]. The rotating motion of solar jets manifests as simultaneous blue-and redshift on the either side of the jet body in doppler velocity maps [88,108,[181][182][183]193].…”
Section: (Ii) Rotating Motionmentioning
confidence: 99%